2008
DOI: 10.1016/j.mcn.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mutations in the glycosylphosphatidylinositol signal peptide of PrP modulate its topology in neuroblastoma cells

Abstract: Point mutations M232R (PrP(232R)), M232T (PrP(232T)), and P238S (PrP(238S)) in the glycosylphosphatidylinositol signal peptide (GPI-SP) of the prion protein (PrP(C)) segregate with familial Creutzfeldt-Jakob disease (CJD). However, the mechanism by which these mutations induce cytotoxicity is unclear since the GPI-SP is replaced by a GPI anchor within 5 min of PrP synthesis and translocation into the endoplasmic reticulum (ER). To examine if mutations in this region interfere with translocation of nascent PrP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Since RbPrP exhibits a large amino acid sequence difference around the site of PrP compared with those from other mammalian species, this may have a significant impact on the GPI anchoring of RbPrP. Moreover, many pathogenic mutations within PrP have been shown to alter the localization and membrane topology of PrP expressed in cultured cells (14,20,40). In this study, we have shown that despite exhibiting a significant amino acid difference around the site compared to PrPs from other mammals, RbPrP is anchored to the plasma membrane through a GPI anchor and is localized to lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…Since RbPrP exhibits a large amino acid sequence difference around the site of PrP compared with those from other mammalian species, this may have a significant impact on the GPI anchoring of RbPrP. Moreover, many pathogenic mutations within PrP have been shown to alter the localization and membrane topology of PrP expressed in cultured cells (14,20,40). In this study, we have shown that despite exhibiting a significant amino acid difference around the site compared to PrPs from other mammals, RbPrP is anchored to the plasma membrane through a GPI anchor and is localized to lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…42 It has been proposed that the two first mutations are related to an increased transmembrane orientation which could explain neurotoxicity. 43 More recently, Guizzunti et al used a chimeric protein expressing EGFP with the SS-GPI of PrP linked to a Myc tag to demonstrate that the P238S mutation in the SS-GPI of PrP prevents degradation of the SS-GPI by the proteasome. As a consequence the cleaved SS-GPI peptide tends to accumulate in the ER.…”
Section: The Signal Sequence Of Gpi (Ss-gpi) As a Sorting Signalmentioning
confidence: 99%
“…Specifically, PrP GPI-SP has been shown to work as an ER-signal sequence when linked to the N-term of GFP. 33 However, when expressed in HeLa cells, cPrP-GPI-SP localized to discrete tubular elements (Fig. 1d), reminiscent of the mitochondrial network.…”
Section: Resultsmentioning
confidence: 97%